TINGKAT SENSITIVITAS HARGA DAN FAKTOR PRODUKSI TERHADAP PENDAPATAN INDUSTRI TEMPE DI KOTA BANJARBARU PROVINSI KALIMANTAN SELATAN - Fitri Mahyudi; Husinsyah Husinsyah (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2018)
This Research aim to know industrial tempe process and to know cost, revenue and tempe operating income. Pursuant to technical of making tempe, entrepreneur do not experience of constraint because entrepreneur have owned procedural knowledge and skill - way of managing the making effort and tempe sale. Produce making tempe during one month with total expense equal to Rp. 33.271.944 and acceptance equal to Rp. 48.600.000, so that the operating income obtained equal to Rp. 15.328.056. Through knowable Sensitivity Analysis that at Production Factor expense go up 5 %, price output descend 5 % and in the situation price output descend 5 % and the Production Factor expense go up 5 % happened the income degradation but the effort making tempe still be run competent